2002
DOI: 10.1002/art.10604
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and sequelae associated with utilization of acetaminophen versus traditional nonsteroidal antiinflammatory drugs in an elderly population

Abstract: Objective. Acetaminophen is recommended as initial therapy for patients with arthritis, particularly those at increased risk of nonsteroidal antiinflammatory drug (NSAID)-induced gastrointestinal (GI) side effects. However, higher doses of acetaminophen inhibit prostaglandin synthesis and have been associated with GI events. This study was undertaken to compare the observed and adjusted rates of GI events (hospitalizations, ulcers, dyspepsia, GI prophylaxis) occurring with higher versus lower doses of acetamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 41 publications
2
46
0
4
Order By: Relevance
“…The RAMQ and Med-Echo databases are linkable through a unique patient identifier. These databases have been used in previous studies (14,15) and have been shown to be valid for pharmacoepidemiologic research (16).…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…The RAMQ and Med-Echo databases are linkable through a unique patient identifier. These databases have been used in previous studies (14,15) and have been shown to be valid for pharmacoepidemiologic research (16).…”
Section: Data Sourcesmentioning
confidence: 99%
“…We chose that period to be 25% of the exposure duration and tested this choice in a sensitivity analysis. Most prescriptions for NS-NSAIDs and celecoxib in Quebec are dispensed with a medication supply for Յ30 days (14,15). Extending the exposure period by 25% of the number of supplied days means that GI hospitalizations that occurred during therapy or up to a week immediately following that therapy would be accounted for.…”
Section: Drug Exposuresmentioning
confidence: 99%
“…The rate of dyspepsia symptoms in the acetaminophen cohort appeared to be dose dependent (1). Thus, patients receiving a daily dose of acetaminophen exceeding 2,600 mg were found to have rates of GI events comparable with those observed in the NSAID cohort, even after adjustment for GI risk susceptibility (1).…”
Section: Concerns About Gastrointestinal Safety Of Acetaminophen: Commentioning
confidence: 56%
“…In a retrospective cohort study, Rahme et al compared the rates of gastrointestinal (GI) events occurring with higher versus lower doses of acetaminophen (1). They concluded that patients receiving higher doses of acetaminophen have higher rates of GI events compared with those receiving lower doses.…”
Section: To the Editormentioning
confidence: 99%
“…In this issue of Arthritis & Rheumatism, Rahme and colleagues report the results of a retrospective cohort analysis that examined rates of adverse GI events in elderly patients treated with NSAIDs or acetaminophen (12). The authors utilized the Government of Quebec Health Care Fund database, which contains demographic, medical, and prescription information on ϳ97% of elderly (age Ն65 years) patients in Quebec.…”
mentioning
confidence: 99%